Effectiveness of Recent Educational Policies in Enhancing Academic Achievement in Lagos State Secondary Schools - Odukoya , Adesola Afusat (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Education remains a central driver of social and economic development, particularly in Lagos State, Nigeria, where secondary schools play a critical role in preparing students for higher education and employment. In recent years, the Lagos State government has introduced multiple policy reforms aimed at enhancing teaching quality, modernising curricula, improving infrastructure, and providing better learning resources. Despite these efforts, the actual impact of these policies on academic achievement—and whether such effects are perceived equally by male and female teachers—remains unclear. This study evaluates the perceived effectiveness of recent educational policies in enhancing student academic achievement in Lagos State secondary schools, with a focus on gender-based perception differences. A quantitative survey research design was employed, targeting public secondary school teachers across various Local Government Areas. Using a structured questionnaire administered to 170 randomly selected teachers, data were analysed through descriptive statistics, Pearson correlation, and independent samples t-tests. Findings revealed a statistically significant positive relationship between the perceived effectiveness of educational policies and student academic achievement (r = 0.372, p = .018), suggesting that well-implemented reforms are associated with improved learning outcomes. No significant difference in perception was observed between male and female teachers, indicating equitable reception of these reforms across genders. The study concludes that targeted educational reforms can positively and consistently influence academic performance when effectively implemented. Its contribution lies in providing empirical, teacher-centred evidence to guide policymakers in refining and sustaining reforms. Recommendations include ongoing policy evaluation, expanded scope to other regions, and inclusion of objective achievement measures in future research.